2018
DOI: 10.1038/s41416-018-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LGR5 in Colorectal Cancer: therapeutic gold or too plastic?

Abstract: Leucine-rich repeat-containing G-protein coupled receptor (LGR5 or GPR49) potentiates canonical Wnt/β-catenin signalling and is a marker of normal stem cells in several tissues, including the intestine. Consistent with stem cell potential, single isolated LGR5+ cells from the gut generate self-organising crypt/villus structures in vitro termed organoids or ‘mini-guts’, which accurately model the parent tissue. The well characterised deregulation of Wnt/β-catenin signalling that occurs during the adenoma-carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 89 publications
3
80
0
1
Order By: Relevance
“…It has been pointed out that there is a difference in LGR5 expression between the adenoma-carcinoma sequence and the serrated neoplasia pathway in RNA in situ hybridization [23] [24]. Because LGR5 is a target of Wnt/ β-catenin signaling that occurs during the adenoma-carcinoma sequence in CRC, LGR5 expression in MMR-P cases, which may involve the adenoma-carcinoma sequence, may be higher than that in MMR-D cases, which may involve the serrated neoplasia pathway [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that there is a difference in LGR5 expression between the adenoma-carcinoma sequence and the serrated neoplasia pathway in RNA in situ hybridization [23] [24]. Because LGR5 is a target of Wnt/ β-catenin signaling that occurs during the adenoma-carcinoma sequence in CRC, LGR5 expression in MMR-P cases, which may involve the adenoma-carcinoma sequence, may be higher than that in MMR-D cases, which may involve the serrated neoplasia pathway [25].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results demonstrate that DCLK1 is linked with functional regulation of the tumor microenvironment and may have potential as a prognostic biomarker and adjuvant target to promote immunotherapy sensitivity in colon and gastric cancer patients.for exposure to pathogens and inflammatory injury in tumor initiation [8][9][10]. In addition, colorectal and stomach epithelium contains LGR5+ stem cells and DCLK1+ tuft cells, both of which have been linked to human GI cancer initiation and progression, and identified as GI cancer cells-of-origin using mouse models [11][12][13][14]. Based on these shared characteristics, it may be possible to identify similar targeting strategies to improve colon and stomach cancer outcomes.Several treatment strategies are employed in GI cancer including surgery, chemotherapy, radiotherapy, and molecularly targeted therapy.…”
mentioning
confidence: 99%
“…for exposure to pathogens and inflammatory injury in tumor initiation [8][9][10]. In addition, colorectal and stomach epithelium contains LGR5+ stem cells and DCLK1+ tuft cells, both of which have been linked to human GI cancer initiation and progression, and identified as GI cancer cells-of-origin using mouse models [11][12][13][14]. Based on these shared characteristics, it may be possible to identify similar targeting strategies to improve colon and stomach cancer outcomes.…”
mentioning
confidence: 99%
“…The precise mechanisms that nely control survival, proliferation, and self-renewal of stem cells remain largely unknown. However, perturbations to this delicate balance leading to an excessive self-renewal would expand the stem cell pool at the base of the crypt, increasing the risk of intestinal tumorigenesis 28,29 . Speci cally, targeted ablation of Lgr5 stem cell population in cancerous tissues revealed that it is dispensable for primary tumor maintenance 30,31 .…”
Section: Discussionmentioning
confidence: 99%